Impact of Implementing Revenue Recognition Based on Psak 72 in the COVID-19 Pandemic Period - Ayunita Ajengtiyas Saputri Mashuri; Ratna Hindria Dyah Pita Sari (Publikasi Indonesia, 2022)
This study was conducted to determine the effect of the application of PSAK 72 as well know as Revenue from contracts with customers. Financial performance using profitability ratios, which is proxied by Return on Assets. In this study, financial performance variables are used to find out more about companies implementing PSAK 72 during the covid 19 pandemic. The objects in this study are companies in the retail, telecommunications, real estate and contractor sectors listed in the IDX-Industrial Classification. The sample was selected using a purposive sampling technique so that the sample obtained was 127 samples during 2020 solely. The software or tool used to test the hypothesis is SPSS version 26. The results of this study result is There is no effect of the application of PSAK 72 in financial performance as measured by profitability ratios. although the implementation of PSAK 72 shows no significant (negative) effect, however, the company has made efforts to prepare for the implementation of PSAK 72 in 2019 by organizing training for its employees and evaluations before finally implementing PSAK 72. Thus, that the implementation of 72 does not have a completely have no on the company's financial performance, this is because the implementation PSAK 72 coincided with the Covid-19 pandemic which also caused the company's revenue to decrease.